The Effect of Seat Back Inclination on Spinal Alignment in Automotive Seating Postures - Sato, Fusako; Miyazaki, Yusuke; Morikawa, Shigehiro; Ferreiro Perez, Antonio; Schick, Sylvia; Brolin, Karin; Svensson, Mats (Frontiers in Bioengineering and Biotechnology, 2021)
Experimental studies have demonstrated a relationship between spinal injury severity and vertebral kinematics, influenced by the initial spinal alignment of automotive occupants. Spinal alignment has been considered one of the possible causes of gender differences in the risk of sustaining spinal injuries. To predict vertebral kinematics and investigate spinal injury mechanisms, including gender-related mechanisms, under different seat back inclinations, it is needed to investigate the effect of the seat back inclination on initial spinal alignment in automotive seating postures for both men and women. The purpose of this study was to investigate the effect of the seat back inclination on spinal alignments, comparing spinal alignments of automotive seating postures in the 20° and 25° seat back angle and standing and supine postures. The spinal columns of 11 female and 12 male volunteers in automotive seating, standing, and supine postures were scanned in an upright open magnetic resonance imaging system. Patterns of their spinal alignments were analyzed using Multidimensional Scaling presented in a distribution map. Spinal segmental angles (cervical curvature, T1 slope, total thoracic kyphosis, upper thoracic kyphosis, lower thoracic kyphosis, lumbar lordosis, and sacral slope) were also measured using the imaging data. In the maximum individual variances in spinal alignment, a relationship between the cervical and thoracic spinal alignment was found in multidimensional scaling analyses. Subjects with a more lordotic cervical spine had a pronounced kyphotic thoracic spine, whereas subjects with a straighter to kyphotic cervical spine had a less kyphotic thoracic spine. When categorizing spinal alignments into two groups based on the spinal segmental angle of cervical curvature, spinal alignments with a lordotic cervical spine showed significantly greater absolute average values of T1 slope, total thoracic kyphosis, and lower thoracic kyphosis for both the 20° and 25° seat back angles. For automotive seating postures, the gender difference in spinal alignment was almost straight cervical and less-kyphotic thoracic spine for the female subjects and lordotic cervical and more pronounced kyphotic thoracic spine for the male subjects. The most prominent influence of seatback inclination appeared in Total thoracic kyphosis, with increased angles for 25° seat back, 8.0° greater in spinal alignments with a lordotic cervical spine, 3.2° greater in spinal alignments with a kyphotic cervical spine. The difference in total thoracic kyphosis between the two seatback angles and between the seating posture with the 20° seat back angle and the standing posture was greater for spinal alignments with a lordotic cervical spine than for spinal alignments with a kyphotic cervical spine. The female subjects in this study had a tendency toward the kyphotic cervical spine. Some of the differences between average gender-specific spinal alignments may be explained by the findings observed in the differences between spinal alignments with a lordotic and kyphotic cervical spine.